Modelling the impact of climate change on groundwater resources : case study of Konya closed basin - Yoloğlu, Onur Cem. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2023., 2023)
The Konya Closed Basin (KCB), located in central Turkey, is one of the major agricultural regions of the country. KCB which has semi-arid climate relies heavily on groundwater for irrigation purposes. This has led to serious decrease in groundwater levels. To enhance water resources management in the basin and ensure its long-term sustainability, a groundwater flow model for the entire basin is developed. The model simulates vertical water flow in the vadose zone as well as horizontal flow in the underlying aquifer system. The model was calibrated using observed head data at 29 monitoring wells from 2000 to 2022. It is estimated that the average water table drop is 0.43 m/year over the entire domain and 0.62 m/year in the agricultural regions. The calibrated model was then used to reveal the potential impacts of climate change on groundwater resources for different water use scenarios. Seventeen regional climate models under two climate pathways (RCP 4.5 and RCP 8.5) were considered for the period of 2023-2040. Five different water management scenarios were developed based on the surveys with farmers, NGOs, and water authorities. With the business as usual scenario, the model predicts 0.28 meters per year average drop in groundwater head over entire basin between 2023 and 2040. On the other hand, through improved irrigation efficiency and reverting to traditional rainfed crops, it is shown that groundwater water drop can be reversed to net increase of 0.04 m/year for the same period allowing for more sustainable use of the groundwater resource.
Keywords: Groundwater -- Konya (Turkey); Climate change.